Gegar Budaya, Adaptasi, dan Konsep Diri Sumber Daya Manusia Pariwisata dalam Menyongsong Era New Normal - Diana Simanjuntak; Rina Fitriana (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
As a business that relies on human mobility, the tourism sector has proven to be severely affected by the Coronavirus disease (COVID-19) pandemic. The paralysis of tourism both nationally and globally as a result of the lockdown policy in various countries and the Large-Scale Social Restriction (LSSR) policy in Indonesia affects the operations of tourism businesses. This has raised high anxiety for Tourism Human Resources about the future of the tourism business. This research discusses culture shock, adaptation, and self-concept of Tourism Human Resources in welcoming the new normal era from a communication perspective, both related to intercultural communication, interpersonal communication, and self-concept as part of communication psychology. This research used a qualitative research method with a case study approach. Data collection techniques were conducted through interviews, field observations, and document study through WhatsApp messages in several professional association groups, webinars, and mass media. The key informants in the research were 14 people as primary data and more than 200 members of the WhatsApp group “Housekeepers Jabar” as secondary data. The results of this research showed that Tourism Human Resources suffered from a culture shock and reached its lowest point in March to mid-April, but rose slowly from late April to June. There are three very stressful aspects of their life, consisting of cultural, social, and economic aspects. Cultural and social aspects are relatively easier to overcome, but the economic aspects are the most impactful because it concerns the sustainability of their life and their families. The period of awareness in the adaptation process is a period of struggle, creativity, and action so that many of them switch professions to run online businesses. This period is still ongoing and it is not known how long it will end. Positive self-concept plays an important role in a person’s success in adapting to survive because it helps a person to be resilient, patient, courageous, and creative in finding solutions in facing challenges thus opening up greater opportunities to successfully solve the problems.